2016
DOI: 10.1371/journal.pone.0159464
|View full text |Cite
|
Sign up to set email alerts
|

Very Long-Term Outcome of Non-Surgically Treated Patients with Temporal Lobe Epilepsy with Hippocampal Sclerosis: A Retrospective Study

Abstract: ObjectiveSurgical intervention can result in complete seizure remission rates of up to 80% in patients with temporal lobe epilepsy with hippocampal sclerosis (TLE-HS). However, certain patients cannot be treated surgically for various reasons. We analyzed the very long-term clinical outcomes of patients with TLE-HS who could not be treated surgically.MethodsSubjects were selected from among patients with TLE-HS who were actively followed up for >10 years and treated with medication without surgical treatment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 23 publications
2
11
0
1
Order By: Relevance
“…We demonstrated that patients with a high frequency of pre-treatment seizure were associated with poor treatment seizure remission (AHR 0.716, 95% CI 0.558, 0.919). In accordance with the present results, previous studies have demonstrated that a higher pre-treatment seizure frequency has been repeatedly associated with a lower chance of remission [19][20][21][22][23][24]. The role of the number of pre-treatment seizure was based on the theory that prolonged and recurrent seizure caused neuronal damage and the development of new epileptic foci [25].…”
Section: Discussionsupporting
confidence: 88%
“…We demonstrated that patients with a high frequency of pre-treatment seizure were associated with poor treatment seizure remission (AHR 0.716, 95% CI 0.558, 0.919). In accordance with the present results, previous studies have demonstrated that a higher pre-treatment seizure frequency has been repeatedly associated with a lower chance of remission [19][20][21][22][23][24]. The role of the number of pre-treatment seizure was based on the theory that prolonged and recurrent seizure caused neuronal damage and the development of new epileptic foci [25].…”
Section: Discussionsupporting
confidence: 88%
“…In a study of 110 patients with MTLE‐HS, 31% remained seizure‐free for at least 2 years . A similar although smaller study reported 29% of 41 patients with MTLE‐HS as being seizure‐free or having only focal aware seizures . These two studies were conducted in nonsurgical cases only.…”
Section: Discussionmentioning
confidence: 99%
“…20 A similar although smaller study reported 29% of 41 patients with MTLE-HS as being seizure-free or having only focal aware seizures. 21 These two studies were conducted in nonsurgical cases only. In contrast, our cases were mostly patients with longstanding disease recruited mainly from tertiary referral centers.…”
Section: Discussionmentioning
confidence: 99%
“…The definitive treatment for refractory MTLE-HS is surgical, with approximately 70–80% of patients achieving seizure freedom post-operatively (Kim et al, 1999; Malmgren and Thom, 2012). Patients may be managed medically if not surgical candidates due to extrahippocampal pathology or if surgery is not an option due to financial constraints (Kurita et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Several studies have examined the prognostic factors associated with the success of medical therapy in MTLE-HS, finding that such treatment results in complete remission in only 5 to 42% of patients, a percentage much lower than that for other forms of epilepsy (Giussani et al, 2016; Kim et al, 1999; Kumlien et al, 2002; Kurita et al, 2016; Kuzmanovski et al, 2016; Semah F et al, 2002; Stephen et al, 2001). Additionally, patients with MTLE-HS may remit and later relapse despite a period of seemingly adequate seizure control (Coan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%